2019
DOI: 10.1002/pc.25204
|View full text |Cite
|
Sign up to set email alerts
|

Hemp hurd and alfalfa as particle filler to improve the thermo‐mechanical and fire retardant properties of poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate)

Abstract: The poor thermo-mechanical and flame-retardant properties of biopolymers are currently limiting their application and potential exploitation as sustainable polymers. The use of agricultural by-products as a functional filler for biopolymers is here presented to address the production of environmentally friendly and economically sustainable biocomposites. To this aim, hemp hurd and alfalfa particles were melt-blended with a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHB) co-polymer. The 30 wt% of filler ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Another interesting new and increasing market for hemp core is in the construction sector, usually combined with lime, where the market share is 16%. Less representative sectors for hemp core fibers are garden much, fungi cultivation and incineration [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting new and increasing market for hemp core is in the construction sector, usually combined with lime, where the market share is 16%. Less representative sectors for hemp core fibers are garden much, fungi cultivation and incineration [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the naturalness of the final product is maintained, the price is decreased proportionally to the filler content and finally, an alternative solution to valorize the agro‐industrial byproducts is offered. Many attempts to utilize agro‐wastes within the plastic words as fillers or different additives have been carried out in the recent past with the common target to expand the biocomposites knowledge and to control and preserve their performances as high as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the physical and mechanical properties of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (P(3HB-co-3HHx)), which is already produced on an industrial scale in 20,000 L reactors by heterotrophic bacteria, namely Aeromonas hydrophila [ 89 ], its rapid degradation by PHA depolymerases can be attributed to its lower crystallinity [ 90 ]; hence, this copolymer can be well-used in disposable products. Its thermo-tolerance and overall mechanical characteristics, such as 150% enhancement in stiffness, were improved with the addition of alfalfa and hemp fibers forming a composite [ 91 ]. This approach is another way of benefiting natural polymers.…”
Section: Bioplasticsmentioning
confidence: 99%
“…Its high biodegradability also makes it ideal for the manufacture of surgical devices and medical material in general, that have short-use life. In tissue regeneration, microfilaments formed by copolymer P (3HB-co-3HV) maintained their masses and other characteristics for up to 12 months after being implanted in rats, being suitable for use as scaffolds [ 91 ]. Studies with PHB biofilms have shown a loss of up to 80% of the initial mass after one year of implantation [ 104 ].…”
Section: Bioplasticsmentioning
confidence: 99%